IMPLEMENTASI SISTEM WAKAF SEBAGAI PILAR PEMBANGUNAN SOSIAL DAN PERTUMBUHAN EKONOMI BERKELANJUTAN DI YORDANIA - Bagaskara Sagita Wijaya; Afni Regita Cahyani Muis; Hesti Rokhaniyah; Aurelia Putri Noveri (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2023)
Waqf, as a form of sharia in Islam, teaches Muslims about the importance of sustainable economic development sources to ensure society's life and welfare. Until now, many Middle Eastern countries have implemented waqf as a form of economic improvement, one of which is Jordan. This research uses a systematic descriptive model with qualitative methods through data collection techniques from journals, books, and online websites that can strengthen the researchers' arguments. Jordan, as one of the countries that adhere to the waqf system, began implementing this system in 1947 and is listed in the laws governing waqf under the auspices of the Ministry of Waqf. Implementing the waqf system has had a very significant impact on the development of public facility development and economic growth in Jordan. Waqf is a form of investment capital that can be invested, the results of which can be enjoyed by many people, so that it becomes an inclusive and sustainable development solution.